Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1088/0957-4484/18/3/035203
|View full text |Cite
|
Sign up to set email alerts
|

Conduction mechanisms and stability of single molecule nanoparticle/molecule/nanoparticle junctions

Abstract: Nanoparticle/molecule/nanoparticle dimer assemblies have been successfully trapped by dielectrophoresis across nanogap electrodes, enabling temperature dependent charge transport measurements through an oligomeric phenylene ethynylene molecule, and transition from direct tunnelling to Fowler-Nordheim tunnelling is observed at approximately 1.5 V. Samples formed by dielectrophoresis show better contact stability than those formed by receding meniscus. The junction shows stable operation over several weeks in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…Ruitenbeek et al then carried out shot noise measurements on the Pt-D 2 -Pt junction formed by the MCBJ technique, and the observed quantum suppression indicated that the junction was indeed formed by just a single molecule. 45,[79][80][81][82][83] …”
Section: Mechanically Controlled Break Junctions (Mcbjs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ruitenbeek et al then carried out shot noise measurements on the Pt-D 2 -Pt junction formed by the MCBJ technique, and the observed quantum suppression indicated that the junction was indeed formed by just a single molecule. 45,[79][80][81][82][83] …”
Section: Mechanically Controlled Break Junctions (Mcbjs)mentioning
confidence: 99%
“…77 With similar nanoparticle-molecule-nanoparticle bridge structures, Parsons et al investigated the conduction mechanisms and stability of single OPE (oligo(p-phenylene ethylenes)) molecules. 79 Furthermore, Jain et al reported a strategy to fabricate 1-2 nm nanogaps via seed-mediated growth of end-to-end linked gold nanorods (AuNRs). 80 Mayor et al demonstrated that the interparticle distance of gold nanoparticle dimers could be controllable by an atomic alteration in the structure of the linker molecule.…”
Section: Electromigration Break Junctions (Ebjs)mentioning
confidence: 99%
“…A different approach was used by groups of Bar-Joseph [42] (see Fig. 2B) and Parsons [43]. These groups synthesized a dimmer structure, consisting of two colloidal gold particles connected by short organic molecules.…”
Section: Dielectrophoretic Manipulation Of Metal and Semiconducting Nmentioning
confidence: 99%
“…These groups synthesized a dimmer structure, consisting of two colloidal gold particles connected by short organic molecules. Then, either dc [42] or ac [43] DEP was used to place dimmers between prefabricated electrodes. Yao and co-workers reported fabrication of a single electron transistor using dielectrophoretic trapping of individual gold NPs [44].…”
Section: Dielectrophoretic Manipulation Of Metal and Semiconducting Nmentioning
confidence: 99%
“…Moreover, the frequency dependence of DEP, which gives rise to other processes such as electro-osmotic and electro-thermal flows, has been shown to affect the deposition of NPs between the electrodes [24][25][26]. Such advances in DEP resulted in the successful bridging of NPs in the electrodes gap [27][28][29].…”
Section: Introductionmentioning
confidence: 99%